Assessment on the urbanization strategy in China: Achievements, challenges and reflections. (January 2018) - Guan, Xingliang; Wei, Houkai; Lu, Shasha; Dai, Qi; Su, Hongjian
Abstract: The "China Dream" is an "Urban Dream". Urbanization is an inevitable requirement for promoting social progress. The Chinese government sees sustainable urbanization as an engine of modernization and economic growth. And the country's urbanization has followed a unique course and is perhaps the greatest human-resettlement experiment in the world history, unprecedentedly transforming the Chinese society in a very short period of time. Yet problems have arisen during the historical process, China's unique path to urbanization has avoided many of pitfalls existing in the developing countries in Africa, Asia and South America. This paper attempts to conclude the good jobs as well as problems in China's urbanizing process which might provide successful experience for the underdeveloped nations and regions to promote urbanization. The most brilliant achievement of urbanization in China is that thousands of years' agriculture-dominated country has ended and a new urbanized country has formed, which only consumed several decades. The country's urban infrastructure, living conditions and public service for urban residents have made great improvements. The fostering urban agglomerations are considered to lead the country's socio-economic transformation and possess the greatest potential for the urbanization and economic growth in the coming decades. In general, the traditional land-centered urbanization in China is a typical "incomplete urbanization" and "low-quality urbanization", presenting impressive characteristics of "four highs and five lows"—high investment, consumption, emission and expansion, and low level, quality, harmony degree, inclusiveness and sustainability. Undoubtedly, the traditional urbanization of China is increasingly difficult to continue and the transformation process should be speeded up as soon as possible. The country should actively explore a people-oriented new-type urbanization way, i.e. an intensive, efficient, rural-urban integration, harmonious and sustainable urbanization model.